2020
DOI: 10.1017/dmp.2020.303
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Emergency Department Utilization During the Early Phase of the COVID-19 Pandemic: Viral Fear or Lockdown Effect?

Abstract: OBJECTIVE: Since the beginning of the COVID-19 pandemic, several frontline workers have expressed their concerns about reduced emergency department (ED) utilization. We aimed to examine the changes in ED utilization during the early phase of the COVID-19 pandemic, in a country with a well-developed primary care system. METHODS: Retrospective analysis of ED utilization in three Dutch hospitals during a 60-day period starting on February 15, 2020. The identical period in 2019 was used as a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
89
0
9

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(104 citation statements)
references
References 9 publications
6
89
0
9
Order By: Relevance
“…Interestingly, an Italian study showed that patients with a suspected breast lesion and those with diagnosed breast cancer frequently refused surgery because of the risk of developing symptoms of COVID-19 [ 26 ]. Furthermore, one retrospective analysis of data from three Dutch hospitals showed that the lockdown in the Netherlands was preceded by decreased emergency department utilization [ 27 ], suggesting that fear may play a significant role in decreasing rates of healthcare utilization. In addition, semi-structured interviews conducted in the United States revealed that patients frequently see hospitals as infectious reservoirs [ 28 ] and may therefore be reluctant to go to hospital or to make an appointment with a primary care physician.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, an Italian study showed that patients with a suspected breast lesion and those with diagnosed breast cancer frequently refused surgery because of the risk of developing symptoms of COVID-19 [ 26 ]. Furthermore, one retrospective analysis of data from three Dutch hospitals showed that the lockdown in the Netherlands was preceded by decreased emergency department utilization [ 27 ], suggesting that fear may play a significant role in decreasing rates of healthcare utilization. In addition, semi-structured interviews conducted in the United States revealed that patients frequently see hospitals as infectious reservoirs [ 28 ] and may therefore be reluctant to go to hospital or to make an appointment with a primary care physician.…”
Section: Discussionmentioning
confidence: 99%
“…16 Although RD repairs and procedures for retinal tears decreased during the COVID-19 pandemic, it is uncertain whether this decrease is fully explained by patients who avoided evaluation and treatment from a fear of COVID-19 infection. 17 Multiple specialties, including emergency medicine, neurosurgery, pediatric orthopedics, and cardiology, have experienced decreases in clinical volumes, with attribution to fear of the virus as well as other specialty-dependent explanations. 7,[18][19][20][21] One of these studies examining approximately 15 000 cases of myocardial infarction demonstrated a decreased rate in myocardial infarction hospitalization within the first 5 weeks of the pandemic, followed by an increase in hospitalization with worse mortality rates.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the fear of viral transmission in hospital settings may explain the significant decrease in emergency admissions, as patients avoid coming into the hospital. [6] As reported by Riley and colleagues, the COVID-19 pandemic led to a significant decrease in the number of surgical complaints, with a 61% decrease in the number of urgent vascular episodes. [7] A shift in vascular disease severity may also account for this reduction in emergent procedures.…”
Section: Discussionmentioning
confidence: 84%